The Synergistic Effect of Time of Exposure, Distance and No Use of Personal Protective Equipment in the Determination of SARS-CoV-2 Infection: Results of a Contact Tracing Follow-Up Study in Healthcare Workers - La Torre, Giuseppe; Marte, Mattia; Previte, Carlo Maria; Barone, Lavinia Camilla; Picchioni, Filippo; Chiappetta, Marta; Faticoni, Augusto; Marotta, Daniela; Mazzalai, Elena; Barletta, Vanessa India; Kibi, Shizuka; Cammalleri, Vittoria; et al. (International journal of environmental research and public health, 2021)
The aim of this study is to assess the effect of contact time, contact distance and the use of personal protective equipment on the determination of SARS-CoV-2 infection in healthcare workers (HCWs). This study consists of an analysis of data gathered for safety reasons at the Sapienza Teaching Hospital Policlinico Umberto I in Rome through the surveillance system that was put into place after the worsening of the COVID-19 pandemic. The studied subjects consist of HCWs who were put under health surveillance, i.e., all employees who were in contact with subjects who were confirmed to have tested positive for SARS-CoV-2. The HCWs under surveillance were monitored for a period encompassing ten days after the date of contact, during which they undertook nasopharyngeal swab tests analysed through RT-PCR (RealStar® SARS-CoV-2 Altona Diagnostic–Germany). Descriptive and univariate analyses have been undertaken, considering the following as risk factors: (a) no personal protective equipment use (PPE); (b) Distance < 1 m between the positive and contact persons; (c) contact time > 15′. Finally, a Cox regression and an analysis of the level of synergism between factors, as specified by Rothman, were carried out. We analysed data from 1273 HCWs. Of these HCWs, 799 (62.8%) were females, with a sample average age of 47.8 years. Thirty-nine (3.1%) tested positive during surveillance. The overall incidence rate was 0.4 per 100 person-days. Time elapsed from the last exposure and a positive RT-PCR result ranged from 2 to 17 days (mean = 7, median = 6 days). In the univariate analysis, a distance <1 m and a contact time > 15′ proved to be risk factors for the SARS-CoV-2 infection, with a hazard ratio (HR) of 2.62 (95% CI: 1.11–6.19) and 3.59 (95% IC: 1.57–8.21), respectively. The synergism analysis found the highest synergism between the “no PPE use” x “Contact time”. The synergy index S remains strongly positive also in the analysis of the factors “no PPE use” x “Distance” and “Time of contact” x “Distance”. This study confirms the absolute need to implement safety protocols during the pandemic and to use the correct PPE within health facilities in order to prevent SARS-CoV-2 infection. The analysis shows that among the factors considered (contact time and distance, no use of PPE), there is a strong synergistic effect.